Sealing paint, preparation method thereof, coating and application thereof

By using a composite system of coupling agent-modified filler solution, macromolecular substances, and sodium carboxymethyl cellulose solution, the problems of cracking, peeling, and sticking of sealing coatings on fiber sealing materials were solved, achieving a stable sealing effect under high temperature and high pressure environments.

CN120818265APending Publication Date: 2025-10-21ZHONGQING FIBER COMPOSITE MATERIALS TECHNOLOGY (LANGFANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511154062.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing sealing coatings are prone to cracking, peeling, and sticking to fiber sealing materials, resulting in poor sealing performance, especially in high temperature and high pressure environments where they are difficult to maintain stability.

Method used

A composite system consisting of a coupling agent-modified filler solution, macromolecules, latex, and a coupling agent-modified sodium carboxymethyl cellulose solution improves the surface smoothness and compatibility of the materials, increases the adhesion between the adhesive lines and the materials, forms strong hydrogen bonds and covalent bonds, and enhances high-temperature performance.

Benefits of technology

It effectively prevents the adhesive lines from cracking and falling off, enhances the anti-sticking effect of the sealing material under high temperature and high pressure, and ensures the stability and reliability of the sealing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818265A_ABST
    Figure CN120818265A_ABST
Patent Text Reader

Abstract

The invention provides a sealing coating, a preparation method thereof, a coating and application thereof, and belongs to the technical field of sealing materials. Pits formed by interweaving the surface fibers can be filled with the filler, so that the adhesive lines are firmly adhered; the filler has heat resistance and has an anti-sticking effect; the coupling agent modified filler solution is adopted, so that the adhesion firmness of the glue line on the surface of the material can be improved; the coupling agent modified sodium carboxymethyl cellulose solution is adopted, so that the hydrophilic performance of macromolecular substances can be reduced, and an adhesive is partially crosslinked under the action of the coupling agent, so that cylinder sticking is avoided; the surface of an uncoated base material adsorbs water, a water molecule film is formed on the surface, after the sealing coating is adopted, a coupling agent is in contact with the water on the surface of the base material and is hydrolyzed to generate a hydroxyl group, the hydroxyl group and a polar hydroxyl group on the surface of the base material are subjected to a condensation reaction to form a hydrogen bond or a-SiO-Me covalent bond, and the water molecule film is formed. An R group in the coupling agent can react with free hydroxyl of rubber to form a net structure, so that rubber lines are prevented from cracking and falling off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sealing materials, and in particular relates to a sealing coating and a preparation method thereof, a coating and an application thereof. Background Art

[0002] After sealing materials are made into gaskets, they are embedded in flange joints to withstand joint movement and act as a sealing medium. Sealing materials are widely used in the joints of various vehicles, mechanical equipment, and various types of pipelines, significantly impacting the performance of vehicles and machinery, as well as safe operation and environmental hygiene during industrial production. Papermaking-based asbestos-free fiber sealing materials are highly efficient and environmentally friendly. Formed using a papermaking process and using water as a medium, they pose a low environmental pollution burden and have significant potential for development. However, when gaskets made from this sealing material are used, problems such as poor flange flatness, high roughness, or excessively low pressure, or when some flat sealing structures have large screw hole spans, poor component rigidity, and uneven sealing pressure distribution, resulting in surface pressure differentials, can lead to poor sealing and leakage. Therefore, in applications where interfacial sealing requirements are high, it is necessary to screen-print a specific glue line on the gasket surface to compensate for the sealing material's insufficient interfacial sealing ability. In these cases, a sealing coating is used to bond the glue line.

[0003] At present, sealing coatings include organic silicone rubber, organic fluorosilicone rubber, nitrile rubber, styrene-butadiene rubber or resin-type sealing coatings, etc. Since the surface micro-roughness of papermaking fiber sealing materials is high and the contact area with the sealing coating is small, and many printed rubber lines have low surface activity and poor bonding performance with the substrate surface, the rubber lines cannot be firmly adhered to the surface of the sealing material, and are prone to cracking and falling off, which reduces the sealing effect. On the other hand, due to the harsh working environment of the sealing gasket, such as being located inside the engine, being in a high temperature, high pressure and close contact environment with the cylinder block and cylinder head for a long time, the rubber in the sealing gasket softens and rheologically sticks to the flange and is difficult to peel off (also known as "sticking to the cylinder"), affecting engine maintenance and the reuse of the gasket. Therefore, how to improve the sealing coating to avoid the cracking, falling off and sticking of the rubber lines has become a technical problem that needs to be solved urgently in this field. Summary of the Invention

[0004] The present invention aims to provide a sealing coating, a preparation method thereof, a coating and an application thereof. The sealing coating provided by the present invention can prevent the glue line from cracking, falling off and sticking to the cylinder.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a sealing coating, which is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0007] The macromolecular substance includes at least one of polyvinyl alcohol, starch, gelatin, casein and casein derivatives;

[0008] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent modified filler solution, and the absolute dry mass of the coupling agent modified sodium carboxymethyl cellulose solution is (1-15): (60-98): (1-25).

[0009] Preferably, the coupling agent in the coupling agent-modified filler solution and the coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution are independently at least one of 3-aminopropyltriethoxysilane, polyethyl silicate, methyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane and titanate coupling agent.

[0010] Preferably, the filler in the coupling agent-modified filler solution is at least one of kaolin, titanium dioxide, talc, barium sulfate, calcium carbonate and silicon dioxide.

[0011] Preferably, the average particle size of the filler in the coupling agent-modified filler solution is less than 10 μm.

[0012] Preferably, the absolute dry mass ratio of the latex to the macromolecular substance is (0.1-5): (95-99.9).

[0013] Preferably, the molecular weight of the sodium carboxymethyl cellulose in the coupling agent-modified sodium carboxymethyl cellulose solution is 10,000 to 200,000.

[0014] Preferably, the solid content of the sealing coating is 10-50%, and the viscosity of the sealing coating is 200-1000 cP.

[0015] The present invention also provides a method for preparing the sealing coating described in the above technical solution, comprising:

[0016] The coupling agent-modified filler solution, macromolecular substance, latex, coupling agent-modified sodium carboxymethyl cellulose solution and solvent are mixed to obtain a sealing coating.

[0017] The present invention also provides a coating, which is obtained by drying the sealing coating described in the above technical solution or the sealing coating prepared by the preparation method described in the above technical solution.

[0018] The present invention also provides the use of the sealing coating described in the above technical solution or the sealing coating prepared by the preparation method described in the above technical solution or the coating described in the above technical solution in fiber sealing materials.

[0019] The invention provides a sealing coating, which is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent; the macromolecular substance comprises at least one of polyvinyl alcohol, starch, gelatin, casein, and a casein derivative; and the ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is (1-25):(60-98):(1-15). The filler particles in the present invention can fill the pits formed by the interweaving of surface fibers, significantly improve the flatness of the material surface, increase the contact area with the rubber line, improve the bonding force between the two, and make the adhesive line adhere more firmly to the material surface; the filler has good heat resistance and will not melt or decompose at high temperatures, and can prevent the rubber component in the material from adhering to the flange after melting, thereby playing an anti-sticking role; the filler solution modified by the coupling agent can increase the compatibility between the filler and the rubber line, and improve the adhesion firmness of the rubber line to the material surface; the sodium carboxymethyl cellulose solution modified by the coupling agent can reduce the hydrophilicity of the macromolecular substance to a certain extent, and under the action of the coupling agent, the adhesive (macromolecule) In addition, when the uncoated substrate surface is exposed to the air, it will absorb moisture in the air and form a thin film of water molecules on the surface. After the sealing coating is applied, the coupling agent comes into contact with the moisture on the substrate surface and hydrolyzes to generate hydroxyl polar groups. The hydroxyl groups further react with the polar groups of the substrate surface to form hydrogen bonds or -SiO-Me covalent bonds, and the R groups in the coupling agent react with the free hydroxyl groups of the rubber to form a mutually penetrating network structure, thereby increasing the surface adhesion to the substrate, thereby significantly improving the bonding ability between the sealing material and the rubber line, and avoiding the cracking and falling off of the rubber line. Experimental results show that when the sealing coating provided by the present invention is coated on the surface of the fiber sealing material, then cut into gaskets and installed on the flange, the material is placed in a 120°C oven for 22 hours, taken out, and allowed to cool to room temperature, the flange is opened using a torque tester, and the peeling force is 0; when the glue line is printed on the surface of the fiber sealing material, the glue line adheres firmly to the surface of the material, and the glue line will not crack, warp or fall off from the material surface when it is scraped by hand or picked off with fingernails. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a photo of a fiber sealing material prepared using the sealing coating of Example 1, cut into gaskets, installed on a flange, and then placed in a 120°C oven for 22 hours before being peeled off;

[0021] Figure 2 The following are photos of glue lines printed on the surface of a fiber sealing material prepared using the sealing coating of Example 1, the glue lines after being scraped by hand, and the glue lines after being picked with fingernails;

[0022] Figure 3 This is a photo of a fiber sealing material prepared using the sealing coating of Example 2, cut into gaskets, installed on a flange, and then placed in a 120°C oven for 22 hours before being peeled off;

[0023] Figure 4 The following are photos of glue lines printed on the surface of a fiber sealing material prepared using the sealing coating of Example 2, the glue lines after being scraped by hand, and the glue lines after being picked with fingernails;

[0024] Figure 5 This is a photo of a fiber sealing material prepared using the sealing coating of Example 3, cut into gaskets, installed on a flange, and then placed in a 120°C oven for 22 hours before being peeled off;

[0025] Figure 6 These are photos of glue lines printed on the surface of a fiber sealing material prepared using the sealing coating of Example 3, and the glue lines after being scraped by hand and picked with fingernails;

[0026] Figure 7 This is a photo of a fiber sealing material prepared using the sealing coating of Example 4, cut into gaskets, installed on a flange, and then placed in a 120°C oven for 22 hours before being peeled off;

[0027] Figure 8 The following are photos of the glue line printed on the surface of the fiber sealing material prepared with the sealing coating of Example 4, the glue line after being scraped by hand, and the glue line after being picked with fingernails;

[0028] Figure 9 This is a photo of a fiber sealing material prepared using the sealing coating of Example 5, cut into gaskets, installed on a flange, and then placed in a 120°C oven for 22 hours before being peeled off;

[0029] Figure 10 The following are photos of the glue line printed on the surface of the fiber sealing material prepared with the sealing coating of Example 5, the glue line after being scraped by hand, and the glue line after being picked with fingernails;

[0030] Figure 11 These are photos of glue lines printed on the surface of a fiber sealing material prepared with the sealing coating of Comparative Example 1, and the glue lines after being scraped by hand and picked with fingernails. DETAILED DESCRIPTION

[0031] The present invention provides a sealing coating, which is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0032] The macromolecular substance includes at least one of polyvinyl alcohol, starch, gelatin, casein and casein derivatives;

[0033] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent modified filler solution, and the absolute dry mass of the coupling agent modified sodium carboxymethyl cellulose solution is (1-15): (60-98): (1-25).

[0034] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0035] The raw materials for preparing the sealing coating of the present invention include a coupling agent-modified filler solution; the coupling agent in the coupling agent-modified filler solution is preferably at least one of 3-aminopropyltriethoxysilane (KH-550), polyethyl silicate, methyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), γ-(methacryloyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane and titanate coupling agent. The filler particles in the present invention can fill the pits formed by the interweaving of surface fibers, significantly improve the flatness of the material surface, increase the contact area with the sealing coating, and improve the bonding force between the two, so that the adhesive line adheres more firmly to the material surface; the filler has good heat resistance and will not melt or decompose at high temperatures. It can prevent the rubber component in the material from melting and adhering to the flange, thereby playing an anti-sticking role; the filler solution modified with a coupling agent can increase the compatibility between the filler and the adhesive line, and improve the adhesion strength of the adhesive line to the material surface.

[0036] As an embodiment, the polyethyl silicate may be polyethyl silicate Si40.

[0037] As an embodiment, the titanate coupling agent may be isopropyl tris(dioctyl pyrophosphate) titanate TC-201.

[0038] As an embodiment, the methyltrimethoxysilane may be methyltrimethoxysilane D20.

[0039] In the present invention, the filler in the filler solution modified by the linker is preferably at least one of kaolin, titanium dioxide, talc, barium sulfate, calcium carbonate and silicon dioxide; and the average particle size of the filler in the filler solution modified by the linker is preferably less than 10 μm.

[0040] In the present invention, when the fillers are kaolin and talc, the mass ratio of the kaolin to talc is preferably (50-70):(30-50).

[0041] In the present invention, when the fillers are kaolin and titanium dioxide, the mass ratio of kaolin to titanium dioxide is preferably (70-90): (10-30).

[0042] In the present invention, when the fillers are calcium carbonate and titanium dioxide, the mass ratio of calcium carbonate to titanium dioxide is preferably (70-80): (20-30).

[0043] In the present invention, the solvent of the coupling agent-modified filler solution is preferably water; the solid content of the coupling agent-modified filler solution is preferably 10 to 70%; and the viscosity of the coupling agent-modified filler solution is preferably 10 to 500 cP.

[0044] As an embodiment, the solid content of the coupling agent-modified filler solution may be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65%; the viscosity of the coupling agent-modified filler solution may be 50cP, 80cP, 95cP, 125cP, 150cP, 200cP, 220cP, 250cP, 300cP, 350cP, 400cP, 440cP or 450cP.

[0045] In the present invention, the method for preparing the coupling agent-modified filler solution is preferably: mixing a solvent and a coupling agent, and then adding a filler to obtain the coupling agent-modified filler solution.

[0046] In the present invention, the mixing of the solvent and the coupling agent is preferably carried out under stirring conditions; the stirring rate is preferably 100 to 3000 rpm; and the stirring time is preferably 5 to 30 minutes. Limiting the stirring process parameters within the above ranges can improve the mixing degree of the raw materials.

[0047] As an embodiment, the stirring rate may be 600 rpm, 1500 rpm, 1600 rpm, 2000 rpm or 2200 rpm; the stirring time may be 10 min, 15 min or 20 min.

[0048] In the present invention, the filler is preferably stirred; the stirring time is preferably 10 to 60 minutes. In one embodiment, the stirring time can be 15 minutes, 20 minutes, 30 minutes, or 40 minutes. The present invention does not specifically limit the stirring rate; operations familiar to those skilled in the art can be used.

[0049] In the present invention, the mass of the coupling agent is preferably 0.1-55% of the mass of the filler. In one embodiment, the mass of the coupling agent can be 1%, 10%, 15%, 20%, 25%, 30%, 35%, 36%, or 40% of the mass of the filler. Limiting the mass of the coupling agent to the above range can further enhance the modification effect, thereby further improving the adhesive properties of the sealing coating.

[0050] The raw materials for preparing the sealing coating of the present invention include macromolecular substances; the macromolecular substances include at least one of polyvinyl alcohol, starch, gelatin, casein, and casein derivatives. In the present invention, the macromolecular substance is a binder used to improve the adhesive properties of the sealing coating.

[0051] In the present invention, when the macromolecular substance is polyvinyl alcohol and starch, the mass ratio of the polyvinyl alcohol to starch is preferably (30-70): (70-30). As an embodiment, the mass ratio of the polyvinyl alcohol to starch can be 50:50.

[0052] In the present invention, the degree of polymerization of the polyvinyl alcohol is preferably 1000-2600; the alcoholysis degree of the polyvinyl alcohol is preferably 88-99%. As an embodiment, the polymer of the polyvinyl alcohol can be 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400 or 2500; the alcoholysis degree of the polyvinyl alcohol can be 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%.

[0053] As an embodiment, the polyvinyl alcohol may be PVA 1788, PVA 1799, PVA2199 or PVA2499.

[0054] In the present invention, the starch is preferably at least one of oxidized starch, enzyme-converted starch and esterified starch.

[0055] The present invention has no particular limitation on the specific type of the casein derivatives, and casein derivatives well known to those skilled in the art may be used.

[0056] The raw materials for preparing the sealing coating of the present invention include latex; the latex is preferably at least one of styrene-butadiene latex, nitrile-butadiene latex, styrene-acrylic latex, and chloroprene latex; the solid content of the latex is preferably 40-50%; and the viscosity of the latex is preferably 20-200 cP. In the present invention, the latex is used as a binder to improve the adhesive properties of the sealing coating.

[0057] As an embodiment, the solid content of the latex may be 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48% or 49%; the viscosity of the latex may be 30cP, 40cP, 50cP, 55cP, 60cP, 65cP, 70cP, 80cP, 90cP, 100cP, 110cP, 120cP, 130cP, 140cP, 150cP, 160cP, 170cP, 180cP or 190cP.

[0058] In the present invention, the absolute dry mass ratio of the latex to the macromolecular substance is preferably (0.1-5):(95-99.9). As an embodiment, the absolute dry mass ratio of the latex to the macromolecular substance can be 0.5:99.5, 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97, 3.5:96.5, 4:96, or 4.5:95.5. By limiting the absolute dry mass ratio of the latex to the macromolecular substance to the above range, the adhesive properties of the sealing coating can be further improved.

[0059] The raw materials for preparing the sealing coating of the present invention include a coupling agent-modified sodium carboxymethyl cellulose solution; the coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution is preferably at least one of 3-aminopropyltriethoxysilane, polyethyl silicate, methyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, and a titanate coupling agent. In the present invention, the coupling agent-modified sodium carboxymethyl cellulose solution can reduce the hydrophilicity of the macromolecular substance to a certain extent. Under the action of the coupling agent, the adhesive (macromolecular substance and latex) is partially cross-linked, thereby improving the high-temperature performance of the sealing coating and preventing sticking to the cylinder.

[0060] As an embodiment, the polyethyl silicate may be polyethyl silicate Si40.

[0061] As an embodiment, the titanate coupling agent may be isopropyl tris(dioctyl pyrophosphate) titanate TC-201.

[0062] As an embodiment, the methyltrimethoxysilane may be methyltrimethoxysilane D20.

[0063] In the present invention, the molecular weight of the sodium carboxymethyl cellulose in the coupling agent-modified sodium carboxymethyl cellulose solution is preferably 10,000 to 200,000. In one embodiment, the molecular weight of the sodium carboxymethyl cellulose can be 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000 or 190,000.

[0064] As an embodiment, the sodium carboxymethyl cellulose may be CMC NX-30, CMC NX-100 or CMCNX-600.

[0065] In the present invention, the solvent of the coupling agent-modified sodium carboxymethyl cellulose solution is preferably water; the solid content of the coupling agent-modified sodium carboxymethyl cellulose solution is preferably 1-10%; and the viscosity of the coupling agent-modified sodium carboxymethyl cellulose solution is preferably 30-1000 cP.

[0066] As an embodiment, the solid content of the coupling agent-modified sodium carboxymethyl cellulose solution may be 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 9.5%; the viscosity of the coupling agent-modified sodium carboxymethyl cellulose solution may be 55cP, 55cP, 100cP, 115cP, 150cP, 180cP, 190cP, 200cP, 250cP, 300cP, 350cP, 370cP, 400cP, 450cP, 500cP, 600cP, 700cP, 800cP or 900cP.

[0067] In the present invention, the method for preparing the coupling agent-modified sodium carboxymethyl cellulose solution is preferably as follows: mixing a solvent and a coupling agent, and then adding sodium carboxymethyl cellulose to obtain the coupling agent-modified sodium carboxymethyl cellulose solution.

[0068] In the present invention, the mixing of the solvent and the coupling agent is preferably carried out under stirring conditions; the stirring rate is preferably 100 to 3000 rpm; and the stirring time is preferably 5 to 30 minutes. Limiting the stirring process parameters within the above ranges can improve the mixing degree of the raw materials.

[0069] As an embodiment, the stirring rate may be 600 rpm, 1200 rpm, 1500 rpm or 1700 rpm; the stirring time may be 15 min, 20 min or 30 min.

[0070] In the present invention, the sodium carboxymethyl cellulose is preferably stirred; the stirring time is preferably 20 to 100 minutes. As an embodiment, the stirring time can be 15 minutes, 20 minutes, 30 minutes, 40 minutes, 60 minutes, or 70 minutes. The present invention does not specifically limit the stirring rate, and operations familiar to those skilled in the art can be used.

[0071] In the present invention, the mass of the coupling agent is preferably 0.1% to 400% of the mass of the sodium carboxymethyl cellulose. As an embodiment, the mass of the coupling agent can be 1%, 7%, 50%, 100%, 150%, 200%, 250%, 300%, 320%, or 350% of the mass of the filler. Limiting the mass of the coupling agent to the above range can further enhance the modification effect, thereby further improving the adhesive properties of the sealing coating.

[0072] The raw materials for preparing the sealing coating of the present invention include a solvent, and the solvent is preferably water. The present invention has no particular limitation on the amount of the solvent, as long as the raw materials are completely dissolved.

[0073] In the present invention, the ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is preferably (1-15): (60-98): (1-25). As an embodiment, the ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution can be (2-10): (65-95): (5-24), and can also be 2:90:8, 5:85:10, 7:70:23, 5:75:20, or 5:80:15. The present invention limits the ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution to the above range, which can further improve the high temperature resistance and adhesive properties of the sealing coating.

[0074] In the present invention, the solid content of the sealing coating is preferably 10-50%; the viscosity of the sealing coating is preferably 200-1000 cP. As an embodiment, the solid content of the sealing coating may be 15%, 17.5%, 18%, 20%, 22%, 25%, 30%, 35%, 40%, or 45%; the viscosity of the sealing coating may be 220 cP, 250 cP, 270 cP, 275 cP, 300 cP, 350 cP, 400 cP, 450 cP, 475 cP, 500 cP, 550 cP, 600 cP, 650 cP, 700 cP, 770 cP, 800 cP, 850 cP, 900 cP, or 950 cP.

[0075] The sealing coating provided by the present invention has an anti-sticking effect. That is, the fiber sealing material applied with the sealing coating is cut into gaskets and installed on the flange. The anti-sticking performance is tested with reference to GB / T 20671.6-2006 (Classification system and test methods for non-metallic gasket materials Part 6 Test method for adhesion of gasket materials to metal surfaces). After being placed in a 120°C oven for 22 hours and taken out and cooled to room temperature, the peeling force when the flange is opened with a torque wrench is 0 (direct peeling without applying external force); the glue line effect is printed on the surface of the coated fiber sealing material. The glue line adheres firmly to the material surface. The glue line will not crack, warp or even fall off from the material surface when scratched by hand or picked with fingernails.

[0076] The sealing coating provided by the present invention uses water as a medium to prepare a water-based coating, does not use toxic or harmful organic solvents, and the raw materials used are all common industrial raw materials, which are cheap and easy to purchase. The preparation process is safe and environmentally friendly, does not emit toxic or harmful substances, and the entire production and use process is environmentally friendly.

[0077] Adsorption theory: When the contact distance between the sealing coating and the substrate surface is less than 1nm, the sealing coating is well adsorbed on the substrate surface under the action of van der Waals force and hydrogen bond, thus forming good interface bonding; the fiber sealing material is coated with surface filler, and the filler particles fill the pits formed by the interweaving of the surface fibers, which significantly improves the flatness of the material surface, increases the contact area with the rubber line, and improves the bonding force between the two, making the rubber line adhere more firmly to the material surface; the filler has good heat resistance and does not melt or decompose at high temperatures. Therefore, when the sealing material is subjected to high temperature and high pressure, the filler can prevent the rubber component in the material from melting and adhering to the flange, playing a certain anti-sticking role.

[0078] Diffusion theory: When the compatibility between the sealing coating molecules and the molecules of the adhered substrate is good, mutual diffusion will occur between the two molecules, causing the interface between them to disappear and forming a strong joint; the sealing coating of the present invention uses a composite coupling agent and a composite adhesive system, and the coupling agent and filler react in the water system. For example, the Si-OH group in the silane coupling agent reacts with the surface of kaolin and the adsorbed -OH. During curing, the hydroxyl group condenses to form a -Si-O- covalent bond, and the filler surface is coated with a layer of coupling agent. The organic polymer group at the other end increases the compatibility between the filler in the coating and the adhesive line, thereby improving the adhesion strength of the adhesive line on the material surface; the macromolecular chain of the macromolecular substance after high-temperature boiling unfolds, and the latex particles are dispersed between the macromolecular chains; the coupling agent is used to modify the surface of sodium carboxymethyl cellulose, The hydrophilicity of macromolecular substances (natural adhesives) is reduced to a certain extent. When the modified sodium carboxymethyl cellulose is mixed with macromolecular substances and latex, the macromolecular substances and latex are partially cross-linked under the action of the coupling agent. In addition, when the surface of the uncoated fiber sealing material is exposed to the air, it will absorb moisture in the air and form a thin film of water molecules on the surface, which is difficult to form adhesion with the hydrophobic components in the rubber line. After the sealing coating is applied, the coupling agent component comes into contact with the moisture on the surface of the substrate and is hydrolyzed to form a hydroxyl polar group. The hydroxyl group further undergoes a condensation reaction with the polar group hydroxyl group on the surface of the substrate to form a hydrogen bond or a -SiO-Me covalent bond, and the R group in the coupling agent reacts with the free hydroxyl group of the rubber to form a mutually penetrating network structure, thereby increasing the surface adhesion to the substrate, and thus the bonding ability of the material and the rubber line is significantly improved.

[0079] The present invention also provides a method for preparing the sealing coating described in the above technical solution, comprising:

[0080] The coupling agent-modified filler solution, macromolecular substance, latex, coupling agent-modified sodium carboxymethyl cellulose solution and solvent are mixed to obtain a sealing coating.

[0081] In the present invention, the mixing of the coupling agent-modified filler solution, the macromolecular substance, the latex, the coupling agent-modified sodium carboxymethyl cellulose solution and the solvent is preferably carried out in the following steps:

[0082] 1) mixing the macromolecular substance, latex and part of the solvent to obtain a mixed material;

[0083] 2) mixing the coupling agent-modified filler solution, the coupling agent-modified sodium carboxymethyl cellulose solution, the mixed material and the remaining solvent.

[0084] In the present invention, the macromolecular substance, latex and part of the solvent are preferably mixed to obtain a mixed material.

[0085] In the present invention, the mixture of the macromolecular substance, latex and part of the solvent is preferably:

[0086] Mix part of the solvent and the macromolecular substance, boil them, and then add the latex.

[0087] The present invention has no particular limitation on the amount of the partial solvent, as long as the raw materials are completely dissolved.

[0088] In the present invention, the mixing of the solvent and the macromolecular substance is preferably carried out under stirring conditions; the stirring rate is preferably 50 to 1000 rpm; and the stirring time is preferably 10 to 60 minutes. Limiting the stirring process parameters within the above ranges can improve the mixing degree of the raw materials.

[0089] As an embodiment, the stirring rate may be 300 rpm, 400 rpm, 500 rpm or 600 rpm; the stirring time may be 15 min, 20 min or 30 min.

[0090] In the present invention, the boiling temperature is preferably 60-95° C. and the boiling time is preferably 30-60 min. The boiling method of the present invention can expand the macromolecular chains of the macromolecular substance and disperse the latex particles between the macromolecular chains.

[0091] As an embodiment, the boiling temperature may be 65°C, 70°C, 75°C, 80°C, 85°C or 90°C; the boiling time may be 40 min or 50 min.

[0092] In the present invention, the latex is preferably added at 40-60° C. As an embodiment, the latex can be added at 50° C. or 55° C. In the present invention, the latex added at 40-60° C. can be better dispersed between macromolecular substances and can also maintain good fluidity of the coating.

[0093] The present invention has no particular limitation on the operation of adding latex, and any operation well known to those skilled in the art may be used.

[0094] In the present invention, the solid content of the mixture is preferably 1-10%; the viscosity of the mixture is preferably 5-300 cP. As an embodiment, the solid content of the mixture may be 2%, 3%, 4%, 5%, 6%, 7%, 8%, or 9%; and the viscosity of the mixture may be 10 cP, 20 cP, 25 cP, 27 cP, 30 cP, 33 cP, 50 cP, 65 cP, 100 cP, or 200 cP.

[0095] After obtaining the mixed material, the present invention preferably mixes the coupling agent-modified filler solution, the coupling agent-modified sodium carboxymethyl cellulose solution, the mixed material and the remaining solvent.

[0096] The present invention has no particular limitation on the amount of the residual solvent, as long as the solid content and viscosity of the final sealing coating meet the required requirements.

[0097] In the present invention, the coupling agent modified filler solution, coupling agent modified sodium carboxymethyl cellulose solution, mixed material and remaining solvent are preferably mixed by: mixing the mixed material and coupling agent modified sodium carboxymethyl cellulose solution, and then adding the coupling agent modified filler solution.

[0098] In the present invention, the mixing of the mixed material and the coupling agent-modified sodium carboxymethyl cellulose solution is preferably carried out under stirring conditions; the stirring time is preferably 5 to 30 minutes. The present invention has no particular limitation on the stirring rate, as long as the raw materials are mixed uniformly.

[0099] As an embodiment, the stirring time can be 10 min, 15 min, 20 min or 25 min.

[0100] In the present invention, the coupling agent-modified filler solution is preferably added under stirring conditions; the stirring time is preferably 10 to 60 minutes. The present invention has no particular limitation on the stirring rate, as long as the raw materials are mixed evenly.

[0101] As an embodiment, the stirring time can be 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min or 55 min.

[0102] The preparation method provided by the invention has simple process.

[0103] The present invention also provides a coating, which is obtained by drying the sealing coating described in the above technical solution or the sealing coating prepared by the preparation method described in the above technical solution.

[0104] The present invention has no special limitation on the drying operation, and the drying process may be performed to a constant weight using the numerical operation known to those skilled in the art.

[0105] The present invention also provides the use of the sealing coating described in the above technical solution or the sealing coating prepared by the preparation method described in the above technical solution or the coating described in the above technical solution in fiber sealing materials.

[0106] In the present invention, the application operation is preferably to coat the sealing coating on the fiber sealing material, followed by drying, cutting and curling.

[0107] In the present invention, the thickness of the fiber sealing material is preferably 0.1 to 3 mm. As an embodiment, the thickness of the fiber sealing material can be 0.5 mm, 1 mm, 1.5 mm, 2 mm or 2.5 mm.

[0108] In the present invention, the coating is preferably rod coating or scraper coating; the coating amount on one side is preferably 1.0 to 10 g / m 2 The double-sided coating amount is preferably 2.0 to 20 g / m 2 .

[0109] The present invention has no particular limitation on the operations of rod coating and doctor blade coating, and operations well known to those skilled in the art may be used.

[0110] As an embodiment, the coating amount on one side can be 2g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 4.5g / m 2 , 5g / m 2 , 5.5g / m 2 , 6g / m 2 , 7g / m 2 , 8g / m 2 or 9g / m 2 The double-sided coating amount can be 3.5g / m 2 4.5g / m 2 , 7g / m 2 , 10g / m 2 , 15g / m 2 or 18g / m 2 .

[0111] In the present invention, the sealing coating is preferably passed through a 60-100 mesh sieve before coating. The present invention has no particular limitation on the operation of passing through a 60-100 mesh sieve, and any operation well known to those skilled in the art can be used.

[0112] In the present invention, the drying is preferably at least one of infrared drying, hot air drying, and cylinder drying; the drying temperature is preferably 80 to 150°C; and the drying time is preferably 10 to 300 seconds. The present invention does not specifically limit the operation of the infrared drying, hot air drying, or cylinder drying, and operations familiar to those skilled in the art may be employed.

[0113] As an embodiment, the drying temperature may be 90°C, 100°C, 105°C, 110°C, 120°C, 125°C, 130°C, 140°C or 145°C; the drying time may be 30s, 50s or 60s.

[0114] The present invention has no particular limitation on the cutting and curling operations, and operations well known to those skilled in the art may be used.

[0115] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0116] Example 1

[0117] A sealing coating is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0118] The coupling agent in the coupling agent-modified filler solution is KH-550, the filler is kaolin, and the average particle size of the filler is less than 10 μm;

[0119] The coupling agent-modified filler solution has a solid content of 35% and a viscosity of 95 cP;

[0120] The macromolecular substance is PVA 1799;

[0121] The latex is styrene-butadiene latex with a solid content of 48% and a viscosity of 65 cP;

[0122] The coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution is KH-560, and the sodium carboxymethyl cellulose is CMC NX-30;

[0123] The coupling agent-modified sodium carboxymethyl cellulose solution has a solid content of 3% and a viscosity of 55 cP;

[0124] The solvent is water;

[0125] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is 2:90:8;

[0126] The preparation method of the sealing coating is:

[0127] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1500 rpm, add silane coupling agent KH-550, continue stirring for 5 minutes after addition, then add kaolin, continue stirring for 15 minutes after addition, to obtain a coupling agent-modified filler solution; wherein the mass of KH-550 is 10% of the mass of kaolin;

[0128] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1000 rpm, add the silane coupling agent KH-560, continue stirring for 30 minutes after the addition, then add CMCNX-30, and continue stirring for 60 minutes to obtain a coupling agent-modified sodium carboxymethyl cellulose solution; wherein the mass of KH-560 is 7% of the mass of CMCNX-30;

[0129] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 300 rpm, add PVA 1799, continue stirring for 20 minutes after the addition, then heat to 95°C and keep warm for 30 minutes for boiling, then cool to 60°C, add styrene-butadiene latex to obtain a mixed material; wherein the absolute dry mass ratio of latex to macromolecular substance is 2:98, the solid content of the mixed coating is 4%, and the viscosity is 33 cP;

[0130] The coupling agent-modified sodium carboxymethyl cellulose solution and the mixed material were added to a mixing tank and mechanically stirred for 5 minutes, and then the coupling agent-modified filler solution was added and mechanically stirred for 20 minutes, and an appropriate amount of water was added to obtain a sealing coating; wherein the sealing coating has a solid content of 17.5% and a viscosity of 475 cP.

[0131] The sealing coating prepared in Example 1 was passed through a 60-mesh screen and applied to the front of the fiber sealing material using a 13# scraper on a coating machine. The hot air drying temperature was 120°C, the drying time was 60s, and the coating amount was 5.5g / m 2 Then apply the reverse side in the same way, the hot air drying temperature is 120℃, the drying time is 60s, and the coating amount is 5.5g / m 2 , the coating amount on both sides is 11g / m 2 .

[0132] The above materials were cut into gaskets and installed on the flange. They were placed in a 120℃ oven for 22 hours. After being taken out and allowed to cool to room temperature, the flange was opened using a torque tester. The peeling force was 0 (directly peeled off without applying external force). The photos after peeling are as follows: Figure 1 shown.

[0133] Print two-component room temperature curing silicone liquid on the surface of the above material to prepare glue lines. Photos of the glue lines after scratching them with hands and picking them with fingernails are shown in the figure below. Figure 2 shown.

[0134] from Figure 2 It can be seen that the glue line is firmly adhered to the material surface and the glue line will not crack, warp or fall off from the material surface.

[0135] Example 2

[0136] A sealing coating is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0137] The coupling agent in the coupling agent-modified filler solution is polyethyl silicate Si40, the filler is kaolin, and the average particle size of the filler is less than 10 μm;

[0138] The coupling agent-modified filler solution has a solid content of 55% and a viscosity of 220 cP;

[0139] The macromolecular substance is starch phosphate;

[0140] The latex is nitrile latex with a solid content of 43% and a viscosity of 70 cP;

[0141] The coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution is KH-550 and the sodium carboxymethyl cellulose is CMC NX-100;

[0142] The coupling agent-modified sodium carboxymethyl cellulose solution has a solid content of 2% and a viscosity of 180 cP;

[0143] The solvent is water;

[0144] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is 5:85:10;

[0145] The preparation method of the sealing coating is:

[0146] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 2000 rpm, add polyethyl silicate Si40, continue stirring for 15 minutes after addition, then add kaolin, continue stirring for 20 minutes after addition, to obtain a coupling agent-modified filler solution; wherein the mass of polyethyl silicate Si40 is 36% of the mass of kaolin;

[0147] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1200 rpm, add silane coupling agent KH-550, continue stirring for 20 minutes after addition, then add CMC NX-100, and continue stirring for 70 minutes to obtain a coupling agent-modified sodium carboxymethyl cellulose solution; wherein the mass of KH-550 is 100% of the mass of CMC NX-100;

[0148] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 600 rpm, add phosphate starch, continue stirring for 30 minutes after the addition, then heat to 91°C and keep warm for 50 minutes for boiling, then cool to 60°C, add nitrile latex with a mass ratio of 3% by mass of phosphate starch, and obtain a mixed material; wherein the absolute dry mass ratio of latex to macromolecular substance is 5:95, the solid content of the mixed coating is 7%, and the viscosity is 65 cP;

[0149] The coupling agent-modified sodium carboxymethyl cellulose solution and the mixed material were added to a mixing tank and mechanically stirred for 15 minutes, and then the coupling agent-modified filler solution was added and mechanically stirred for 30 minutes, and an appropriate amount of water was added to obtain a sealing coating; wherein the sealing coating has a solid content of 35% and a viscosity of 770 cP.

[0150] The sealing coating prepared in Example 2 was passed through a 60-mesh screen and applied to the front of the fiber sealing material using a 0# scraper. The hot air drying temperature was 120°C, the drying time was 30s, and the coating amount was 7g / m 2 Then apply the reverse side in the same way, the hot air drying temperature is 110℃, the drying time is 45s, and the coating amount is 7g / m 2 , the coating amount on both sides is 14g / m 2 .

[0151] The above materials were cut into gaskets and installed on the flange. They were placed in a 120℃ oven for 22 hours. After being taken out and allowed to dry to room temperature, the flange was opened using a torque tester. The peeling force was 0. The photos after peeling are as follows. Figure 3 shown.

[0152] Print fluorosilicone lines on the surface of the above materials, and take photos of the lines after scraping them with your hands and picking them with your fingernails. Figure 4 shown.

[0153] from Figure 4 It can be seen that the glue line is firmly adhered to the material surface and the glue line will not crack, warp or fall off from the material surface.

[0154] Example 3

[0155] A sealing coating is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0156] The coupling agent in the coupling agent-modified filler solution is isopropyl tris(dioctyl pyrophosphate acyloxy) titanate TC-201, the filler is kaolin and talc, the mass ratio of kaolin to talc is 70:30, and the average particle size of the filler is less than 10 μm;

[0157] The coupling agent-modified filler solution has a solid content of 40% and a viscosity of 440 cP;

[0158] The macromolecular substance is gelatin;

[0159] The latex is styrene acrylic latex with a solid content of 45% and a viscosity of 80 cP;

[0160] The coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution is methyltrimethoxysilane D20, and the sodium carboxymethyl cellulose is CMC NX-600;

[0161] The coupling agent-modified sodium carboxymethyl cellulose solution has a solid content of 3% and a viscosity of 370 cP;

[0162] The solvent is water;

[0163] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is 7:70:23;

[0164] The preparation method of the sealing coating is:

[0165] Add an appropriate amount of water to a preparation tank, start mechanical stirring at 2200 rpm, add the silane coupling agent isopropyl tris(dioctyl pyrophosphate) titanate TC-201, continue stirring for 20 minutes after the addition, then add kaolin and talc, continue stirring for 20 minutes after the addition, to obtain a coupling agent-modified filler solution; wherein the mass of isopropyl tris(dioctyl pyrophosphate) titanate TC-201 is 35% of the total mass of kaolin and talc;

[0166] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1700 rpm, add methyltrimethoxysilane D20 as a silane coupling agent, continue stirring for 15 minutes after the addition, then add CMCNX-600, and continue stirring for 60 minutes to obtain a coupling agent-modified sodium carboxymethyl cellulose solution; wherein the mass of methyltrimethoxysilane D20 is 100% of the mass of CMCNX-600;

[0167] Add an appropriate amount of water to a preparation tank, start mechanical stirring at a speed of 600 rpm, add gelatin, continue stirring for 30 minutes after addition, then heat to 60°C and keep warm for 60 minutes for boiling, then cool to 50°C, add styrene acrylic latex at a concentration of 1% by weight of gelatin to obtain a mixed material; wherein the absolute dry mass ratio of latex to macromolecular substance is 2:98, the solid content of the mixed coating is 9%, and the viscosity is 25 cP;

[0168] The coupling agent-modified sodium carboxymethyl cellulose solution and the mixed material were added to a mixing tank and mechanically stirred for 20 minutes, and then the coupling agent-modified filler solution was added and mechanically stirred for 40 minutes, and an appropriate amount of water was added to obtain a sealing coating; wherein the sealing coating had a solid content of 22% and a viscosity of 275 cP.

[0169] The sealing coating prepared in Example 3 was passed through a 60-mesh screen and applied to the front of the fiber sealing material using a 13# scraper. The hot air drying temperature was 105°C, the drying time was 50s, and the coating amount was 4.5g / m 2 Then apply the reverse side in the same way, dry with hot air at 105℃ for 25s, then dry with a drying cylinder at 85℃ for 15s, with a coating weight of 4.5g / m 2 , the coating amount on both sides is 9g / m 2 .

[0170] The above materials were cut into gaskets and installed on the flange. They were placed in a 120℃ oven for 22 hours. After being taken out and allowed to cool to room temperature, the flange was opened using a torque tester. The peeling force was 0 (directly peeled off without applying external force). The photos after peeling are as follows: Figure 5 shown.

[0171] Print acrylic resin glue lines on the surface of the above materials, and take photos of the glue lines after scraping them with your hands and picking them with your fingernails. Figure 6 shown.

[0172] from Figure 6 It can be seen that the glue line is firmly adhered to the material surface and the glue line will not crack, warp or fall off from the material surface.

[0173] Example 4

[0174] A sealing coating is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0175] The coupling agent in the coupling agent-modified filler solution is KH-550, the fillers are kaolin and titanium dioxide, the mass ratio of kaolin and titanium dioxide is 90:10, and the average particle size of the filler is less than 10 μm;

[0176] The coupling agent-modified filler solution has a solid content of 30% and a viscosity of 80 cP;

[0177] The macromolecular substances are PVA1799 and oxidized starch, and the mass ratio of the two is 50:50;

[0178] The latex is chloroprene latex with a solid content of 40% and a viscosity of 55 cP;

[0179] The coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution is polyethyl silicate Si40, and the sodium carboxymethyl cellulose is CMC NX-100;

[0180] The coupling agent-modified sodium carboxymethyl cellulose solution has a solid content of 2.5% and a viscosity of 190 cP;

[0181] The solvent is water;

[0182] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is 5:75:20;

[0183] The preparation method of the sealing coating is:

[0184] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1600 rpm, add silane coupling agent KH-550, continue stirring for 10 minutes after addition, then add kaolin and titanium dioxide, continue stirring for 20 minutes after addition, to obtain a coupling agent-modified filler solution; wherein the mass of KH-550 is 40% of the total mass of kaolin and titanium dioxide;

[0185] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1200 rpm, add polyethyl silicate Si40, continue stirring for 20 minutes after addition, then add CMC NX-100, and continue stirring for 60 minutes to obtain a coupling agent-modified sodium carboxymethyl cellulose solution; wherein the mass of polyethyl silicate Si40 is 150% of the mass of CMC NX-100;

[0186] Add an appropriate amount of water to a preparation tank, start mechanical stirring at a speed of 400 rpm, add PVA 1799 and oxidized starch, continue stirring for 30 minutes after addition, then heat to 95°C and keep warm for 30 minutes for boiling, then cool to 60°C, add chloroprene rubber latex with a total weight of 3% of PVA1799 and oxidized starch to obtain a mixed material; wherein the absolute dry weight ratio of latex to macromolecular substance is 5:95, the solid content of the mixed coating is 3%, and the viscosity is 27 cP;

[0187] The coupling agent-modified sodium carboxymethyl cellulose solution and the mixed material were added to a mixing tank and mechanically stirred for 15 minutes, and then the coupling agent-modified filler solution was added and mechanically stirred for 45 minutes, and an appropriate amount of water was added to obtain a sealing coating; wherein the sealing coating has a solid content of 20% and a viscosity of 270 cP.

[0188] The sealing coating prepared in Example 4 was passed through an 80-mesh screen and applied to the front of the fiber sealing material using a scraper on a coating machine. The hot air drying temperature was 105°C, the drying time was 50s, and the coating amount was 3.5g / m 2Then apply the reverse side in the same way, the hot air drying temperature is 105℃, the drying time is 50s, and the coating amount is 3.5g / m 2 , coating amount on both sides totals 7g / m 2 .

[0189] The above materials were cut into gaskets and installed on the flange. They were placed in a 120℃ oven for 22 hours. After being taken out and allowed to cool to room temperature, the flange was opened using a torque tester. The peeling force was 0 (directly peeled off without applying external force). The photos after peeling are as follows: Figure 7 shown.

[0190] Print silicone resin glue lines on the surface of the above materials, and take photos of the glue lines after scraping them with your hands and picking them with your fingernails. Figure 8 shown.

[0191] from Figure 8 It can be seen that the glue line is firmly adhered to the material surface and the glue line will not crack, warp or fall off from the material surface.

[0192] Example 5

[0193] A sealing coating is prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent;

[0194] The coupling agent in the coupling agent-modified filler solution is polyethyl silicate Si40, the filler is calcium carbonate and titanium dioxide, the mass ratio of calcium carbonate to titanium dioxide is 80:20, and the average particle size of the filler is less than 10 μm;

[0195] The coupling agent-modified filler solution has a solid content of 35% and a viscosity of 125 cP;

[0196] The macromolecular substance is PVA 1799;

[0197] The latex is nitrile latex with a solid content of 44% and a viscosity of 90 cP;

[0198] The coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution is polyethyl silicate Si40, and the sodium carboxymethyl cellulose is CMC NX-600;

[0199] The coupling agent-modified sodium carboxymethyl cellulose solution has a solid content of 1.8% and a viscosity of 115 cP;

[0200] The solvent is water;

[0201] The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent-modified filler solution, and the absolute dry mass of the coupling agent-modified sodium carboxymethyl cellulose solution is 5:80:15;

[0202] The preparation method of the sealing coating is:

[0203] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 2000 rpm, add polyethyl silicate Si40, continue stirring for 15 minutes after addition, then add calcium carbonate and titanium dioxide, continue stirring for 30 minutes after addition, to obtain a coupling agent-modified filler solution; wherein the mass of polyethyl silicate Si40 is 40% of the total mass of calcium carbonate and titanium dioxide;

[0204] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 1000 rpm, add polyethyl silicate Si40, continue stirring for 15 minutes after the addition, then add CMC NX-600, and continue stirring for 60 minutes to obtain a coupling agent-modified sodium carboxymethyl cellulose solution; wherein the mass of polyethyl silicate Si40 is 100% of the mass of CMC NX-600;

[0205] Add an appropriate amount of water to the preparation tank, start mechanical stirring at a speed of 500 rpm, add PVA 1799, continue stirring for 20 minutes after the addition, then heat to 95°C and keep warm for 30 minutes for boiling, then cool to 60°C, add nitrile latex with a mass% of PVA1799 to obtain a mixed material; wherein the absolute dry mass ratio of latex to macromolecular substance is 2:98, the solid content of the mixed coating is 5%, and the viscosity is 33 cP;

[0206] The coupling agent-modified sodium carboxymethyl cellulose solution and the mixed material were added to a mixing tank and mechanically stirred for 20 minutes, and then the coupling agent-modified filler solution was added and mechanically stirred for 40 minutes, and an appropriate amount of water was added to obtain a sealing coating; wherein the sealing coating has a solid content of 18% and a viscosity of 220 cP.

[0207] The sealing coating prepared in Example 5 was passed through an 80-mesh screen and applied to the front of the fiber sealing material using a scraper on a coating machine. The hot air drying temperature was 125°C, the drying time was 30s, and the coating amount was 4g / m 2 Then apply the reverse side in the same way, the hot air drying temperature is 105℃, the drying time is 60s, and the coating amount is 4g / m 2 , the coating amount on both sides is 8g / m 2 .

[0208] The above materials were cut into gaskets and installed on the flange. They were placed in a 120℃ oven for 22 hours. After being taken out and allowed to dry to room temperature, the flange was opened using a torque tester. The peeling force was 0. The photos after peeling are as follows. Figure 9 shown.

[0209] Print silicone resin glue lines on the surface of the above materials, and take photos of the glue lines after scraping them with your hands and picking them with your fingernails. Figure 10 shown.

[0210] from Figure 10 It can be seen that the glue line is firmly adhered to the material surface and the glue line will not crack, warp or fall off from the material surface.

[0211] Comparative Example 1

[0212] Kaolin was added to water and dispersed at high speed for 30 minutes. Then, the prepared PVA1799 solution (10% by weight of kaolin) and the dissolved CMC NX-100 solution (10% by weight of kaolin) and calcium stearate lubricant (20% by weight of kaolin) were added and stirred at medium speed for 20 minutes to obtain a control coating.

[0213] Apply the coating to the surface of the fiber sealing material with a scraper and dry it with hot air at 105℃ for 90s.

[0214] The above material was cut into gaskets and installed on the flange. They were placed in a 120°C oven for 22 hours, taken out, and allowed to dry to room temperature. The flange was opened with a torque tester, and the peeling force was.

[0215] Print fluorosilicone rubber liquid on the surface of the above material, and after curing, scratch it with your hands and pick the glue line with your fingernails. Figure 11 shown.

[0216] from Figure 11 It can be seen that the glue line does not adhere firmly to the material surface and the glue line is easy to crack and fall off.

[0217] It can be seen from the examples and comparative examples that the sealing coating provided by the present invention can prevent the glue line from cracking, falling off and sticking to the cylinder.

[0218] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A sealing coating prepared from the following raw materials: a coupling agent-modified filler solution, a macromolecular substance, latex, a coupling agent-modified sodium carboxymethyl cellulose solution, and a solvent; The macromolecular substance includes at least one of polyvinyl alcohol, starch, gelatin, casein and casein derivatives; The ratio of the total absolute dry mass of the macromolecular substance and latex, the absolute dry mass of the coupling agent modified filler solution, and the absolute dry mass of the coupling agent modified sodium carboxymethyl cellulose solution is (1-15): (60-98): (1-25).

2. The sealing coating according to claim 1, characterized in that The coupling agent in the coupling agent-modified filler solution and the coupling agent in the coupling agent-modified sodium carboxymethyl cellulose solution are independently at least one of 3-aminopropyltriethoxysilane, polyethyl silicate, methyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane and titanate coupling agent.

3. The sealing coating according to claim 1, characterized in that The filler in the coupling agent-modified filler solution is at least one of kaolin, titanium dioxide, talc, barium sulfate, calcium carbonate and silicon dioxide.

4. The sealing coating according to claim 1 or 3, characterized in that: The average particle size of the filler in the coupling agent-modified filler solution is less than 10 μm.

5. The sealing coating according to claim 1, characterized in that The absolute dry mass ratio of the latex to the macromolecular substance is (0.1-5):(95-99.9).

6. The sealing coating according to claim 1, characterized in that The molecular weight of the sodium carboxymethyl cellulose in the coupling agent-modified sodium carboxymethyl cellulose solution is 10,000-200,000.

7. The sealing coating according to claim 1, characterized in that The solid content of the sealing coating is 10-50%, and the viscosity of the sealing coating is 200-1000 cP.

8. A method for preparing the sealing coating according to any one of claims 1 to 7, comprising: The coupling agent-modified filler solution, macromolecular substance, latex, coupling agent-modified sodium carboxymethyl cellulose solution and solvent are mixed to obtain a sealing coating.

9. A coating obtained by drying the sealing coating according to any one of claims 1 to 7 or the sealing coating prepared by the preparation method according to claim 8.

10. Use of the sealing coating according to any one of claims 1 to 7, or the sealing coating prepared by the preparation method according to claim 8, or the coating according to claim 9 in fiber sealing materials.